Investigation of the influence of the concentration of the shungite filler on the optical properties, morphology and molecular structure of the polyimide film - Muradov, A.D.; Yar-Mukhamedova, G.Sh.; Mukhambetova, S.B.; Cheryazdanov, K.B.; Amyrkhanova, K.M.; Alyeva, Zh.A. (Recent Contributions to Physics, 2018)
In the present work, the influence of the concentration of shungite filler on surface morphology, optical properties, molecular structure of polyimide films was investigated. Shungite was used in four different concentrations. In all the samples obtained, changes can be traced depending on the concentration of the filler. The surface of the film becomes smoother with increasing filler concentration. The addition of filler does not greatly affect the photoluminescent spectrum of the films, since the polyimide has a high resistance to radiation. One of the main properties of polyimide is high resistance to heat, resistance to radiation, stability in organic solutions and other valuable properties. For the analysis of structural elements, the Raman scattering method was used. Investigation of the morphology of the surface of polyimide films is carried out using an atomic force microscope. The size of the shungite filler was determined using an optical microscope Leica DM 6000 M. Due to the inhomogeneity of shungite concentrations, a graph of the change in the transmission coefficient of light is given. Under normal conditions of mechanical stress, as well as for polyimide, mechanical and physical quantities, methods for studying the influence of mechanical weight are considered. As a result of studies of the strength of a polyimide film, as well as a change in the optical properties, we determined that the optical and mechanical properties of polyimide films depend not only on the appearance of the filler but also on its concentration.